2020
DOI: 10.1007/s10029-020-02270-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning inguinal hernia repair? A survey of current practice and of preferred methods of surgical residents

Abstract: Purpose During surgical residency, many learning methods are available to learn an inguinal hernia repair (IHR). This study aimed to investigate which learning methods are most commonly used and which are perceived as most important by surgical residents for open and endoscopic IHR. Methods European general surgery residents were invited to participate in a 9-item web-based survey that inquired which of the learning methods were used (checking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Nazari et al, reported from a survey in which surgery residents from 19 European countries participated, that 59.2% of them had no experience on LIHR. 12 Our study showed that one fourth of the participants finished the residency before 1990, and therefore, they were not trained when modern laparoscopic surgery began. One fifth of them, finished the residency within the five years previous of the survey, so they were trained fully in laparoscopic era.…”
Section: Discussionmentioning
confidence: 74%
“…Nazari et al, reported from a survey in which surgery residents from 19 European countries participated, that 59.2% of them had no experience on LIHR. 12 Our study showed that one fourth of the participants finished the residency before 1990, and therefore, they were not trained when modern laparoscopic surgery began. One fifth of them, finished the residency within the five years previous of the survey, so they were trained fully in laparoscopic era.…”
Section: Discussionmentioning
confidence: 74%
“…UK/Europe: No published data on the rates of LIHRs in the UK or Europe could be found. A survey published in Hernia in 2020 showed that only 52.9% of European surgical residents had experience with LIHRs during training 13 . Data from the rest of the world are lacking.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve competency within training, a more efficient teaching syllabus needs to be developed beyond the apprenticeship model in the operating theatre. Video demonstration and hands on hernia courses have been reported to be perceived by trainees as the most important learning methods, 13 and additionally simulator‐based training and video analysis have been shown to be effective 21,26 . A standardized curriculum model along the lines of a ‘Hernia School’ involving anatomy, procedure steps, intraoperative decision making and simulation enhanced technical skills training is required.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, there are real challenges for training and surgery proficiency such as working legislation, legal and ethical concerns, and lack of proctors and simulation opportunities [ 17 ]. The three most important learning methods for hernia repair are participation in the OR and video-demonstrations followed by hands-on hernia courses [ 25 ]. That highlights the importance of hands-on simulation and the need to be widely accessible to residents and surgeons meaning that models should be low-cost and with low logistics; valuable from an educational point-of-view; and suitable for procedure and skills assessment.…”
Section: Discussionmentioning
confidence: 99%